An Enquiry into how Political Sufi-Regimes Evolve in Contemporary Bangladesh (Journal of the Asiatic Society of Bangladesh, Humanities, 2023)
Contrary to the commonly held notion that Sufis are generally apolitical, contemporary scholars on Sufism, in general, have reached a consensus that Sufism has always been tinged with political colour. However, this perspective, though dominant, seems to under-appreciate the nuances of Sufism and at the same time denies Sufis' capacity to remain non-partisan whenever they choose to be. Against this backdrop, this article attempts to investigate four Sufi-regimes that have been politically active in contemporary Bangladesh. Analysing their evolution, it explains the stage in their growth when such regimes are likely to remain non-partisan and when they are likely to shed their visibly apolitical stance, take noticeably more political positions and/or form political party. It argues that before taking on an explicitly political character, a typical Sufi-regime usually undergoes at least three identifiable phases – namely, recognition, expansion and stabilisation, and lastly discipline through organisation. According to the analytical model presented here, Sufis in the recognition and expansion phase are unlikely to join politics, while those with a disciplined group of followers and murids can participate in the political process with a minimum level of encouragement from their respective surroundings.Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 68(1), 2023, pp. 1-32